Micro Efficiency and Macro Growth - Nallari, Raj; Bayraktar, Nihal (2012)
This paper is about micro foundations of productivity and growth. There are several studies on productivity for advanced economies but relatively few for developing countries. Using data from the investment climate surveys of the World Bank, estimation results from 45 developing countries, complemented by extended analysis at firm and industry levels for Brazil and India for the period 2002-05, indicate the following: (i) confirmation of the importance of total factor productivity at firm, industry and national levels, but total factor productivity progressively tapers off at each level of aggregation implying that there is a less than one-to-one relationship between micro-efficiency, sector growth, and macro growth; (ii) capital accumulation is more important at the macro level than the micro level; (iii) productivity at the micro level is driven by research and development, the capacity utilization rate, and adoption of foreign technology (all of which involve management decisions), and is negatively related to corruption and instability, tax, and financial regulations; and (iii) confirmation of the lower contribution of total factor productivity to output growth in developing countries than in developed economies. Management decisions are involved in a lot of day-to-day operations at the firm level and therefore management is an unmeasured input. In developing countries, at the firm level, there is a need to understand the contribution of quality of inputs (management quality, education and labor quality, training, experience of workers, use of computers at work) and also the role of external agglomeration (for example, location in a booming city, competitive pressures from new firms, trade competition, and regulations).